Nonvisual multisensory impairment of body perception in anorexia nervosa: a systematic review of neuropsychological studies. - Santino Gaudio; Samantha Jane Brooks; Giuseppe Riva (PLoS ONE)
Background Body image distortion is a central symptom of Anorexia Nervosa (AN). Even if corporeal awareness is multisensory majority of AN studies mainly investigated visual misperception. We systematically reviewed AN studies that have investigated different nonvisual sensory inputs using an integrative multisensory approach to body perception. We also discussed the findings in the light of AN neuroimaging evidence. Methods PubMed and PsycINFO were searched until March, 2014. To be included in the review, studies were mainly required to: investigate a sample of patients with current or past AN and a control group and use tasks that directly elicited one or more nonvisual sensory domains. Results Thirteen studies were included. They studied a total of 223 people with current or past AN and 273 control subjects. Overall, results show impairment in tactile and proprioceptive domains of body perception in AN patients. Interoception and multisensory integration have been poorly explored directly in AN patients. A limitation of this review is the relatively small amount of literature available. Conclusions Our results showed that AN patients had a multisensory impairment of body perception that goes beyond visual misperception and involves tactile and proprioceptive sensory components. Furthermore, impairment of tactile and proprioceptive components may be associated with parietal cortex alterations in AN patients. Interoception and multisensory integration have been weakly explored directly. Further research, using multisensory approaches as well as neuroimaging techniques, is needed to better define the complexity of body image distortion in AN. Key findings The review suggests an altered capacity of AN patients in processing and integration of bodily signals: body parts are experienced as dissociated from their holistic and perceptive dimensions. Specifically, it is likely that not only perception but memory, and in particular sensorimotor/proprioceptive memory, probably shapes bodily experience in patients with AN.